2020
DOI: 10.1002/pan3.10142
|View full text |Cite
|
Sign up to set email alerts
|

Local knowledge, know‐how and knowledge mobilized in a globalized world: A new approach of indigenous local ecological knowledge

Abstract: More than 30 years after the 1988 Declaration of Belém, which we can consider an important outcome of socio‐environmental movements, this reflexive paper proposes new ways of approaching indigenous local knowledge (ILK) related to the living environment and understanding its relevance in times of global socio‐environmental crisis. Drawing upon the example of an ethnodevelopment project based on guarana production by indigenous Sateré‐Mawé people in the Brazilian Amazon, two important issues are addressed. Firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 71 publications
1
16
0
Order By: Relevance
“…This finding supports previous studies in the region that report Indigenous organizations using their traditional knowledge to shape the dynamic on how economic development and global markets (e.g. tourism and agribusinesses) interact with their traditional food systems (Congretel & Pinton, 2020;Coq-Huelva et al, 2018;Sidali et al, 2016).…”
Section: Discussionsupporting
confidence: 90%
“…This finding supports previous studies in the region that report Indigenous organizations using their traditional knowledge to shape the dynamic on how economic development and global markets (e.g. tourism and agribusinesses) interact with their traditional food systems (Congretel & Pinton, 2020;Coq-Huelva et al, 2018;Sidali et al, 2016).…”
Section: Discussionsupporting
confidence: 90%
“…Line‐transect surveys are based on theoretical scientific knowledge, characterized by being systematic, controlled and based on hypotheses; which provides objectivity, verifiability, and, when properly applied, precision and accuracy (Rodríguez & Pérez, 2017). On the other hand, LEK arises from day‐to‐day practices and empirical knowledge embedded within specific worldviews beyond the nature/culture divide (Congretel & Pinton, 2020; Rodríguez & Pérez, 2017). LEK has direct practical applications and is considered more inductive and tacit (Congretel & Pinton, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Multiscale studies have revealed the role of indigenous perceptions and beliefs in the way local communities control soil erosion and fertility, manage land use and forest regeneration in secondary fallows (Barrera-Bassols et al, 2006;Carrière, 2002). All these studies emphasise how studying local knowledge of plants species helps understand human/nature interactions, and why such knowledge play a critical role in the resilience of socio-ecological systems (Congretel & Pinton, 2020;Folke, 2004).…”
Section: Introductionmentioning
confidence: 99%